Preeclampsia is associated with hypermethylation of IGF-1 promoter mediated by DNMT1 - Ma, Min (Am J Transl Res, 2018)
Previous studies have demonstrated a dynamic epigenetic regulation of genes expression in placenta trophoblasts and a dynamic imbalance of DNA methylation and hydroxymethylation. Reduced IGF-1 has been observed in preeclampsia. This study was to investigate the interactive roles between IGF-1 and the global DNA methylation/hydroxymethylation, and the status of DNA methylation/hydroxymethylation and associated enzymes such as DNMTs and TETs in peeeclamptic placentas and hypoxic trophoblasts. It was found that IGF-1 was decreased in preeclamptic placentas and hypoxic trophoblasts when compared to the control group using immunohistochemisty, western blot, qRT-PCR and ELISA. Pyrophosphate sequencing showed IGF-1 promoter was significantly hypermethylated in preeclamptic placentas, which was responsible for reduced IGF-1 expression. Preeclamptic placentas and hypoxic trophoblasts were hypermethylated and hypohydroxymethylated accompanied by remarkably higher 5mC, DNMT1 and DNMT3b, and lower DNMT3a, 5hmC, TET1, TET2 and TET3 detected by immunohistochemisty, western blot, qRT-PCR and ELISA. Pearson’s correlation confirmed a statistically significant negative correlation between IGF-1 and DNMT1. Furthermore, both treatment with 5-Aza-dc and DNMT1-siRNA significantly increased the expression of IGF-1 in HTR8 cells, indicating the potential mechanism of DNMT1-mediated DNA methylation in IGF-1 regulation. However, IGF-1 didn’t change DNA methylation or hydroxymethylation. These findings suggest that preeclampsia is associated with hypermethylation of IGF-1 promoter mediated by DNMT1 and provide new insights into the diagnosis and treatment of preeclampsia.